Synchronization Regulation Debt Collector Industry Finance in Indonesia - Daniel Constantyn Adam (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Financial Industry in Indonesia in providing credit facilities or financing facilities for debtors will definitely require debt collection activities from debtors who have defaulted in the context of recovering receivables from debtors. Who in this activity usually collaborate and or authorize debt collectors to carry out the collection function. However, in reality in the field there are many violations of the law committed by debt collectors and based on the analysis conducted in the study, it was found that one of the causes was due to regulatory conditions or regulations from Bank Indonesia (PBI) and the Financial Services Authority (POJK) regulations regarding debt collectors only apply binding on the financial industry as service users of debt collectors and not binding directly on each individual debt collector due to the limited regulatory authority of the two financial industry regulators who are only entitled to regulate the financial industry as stipulated in the existing laws and regulations. Therefore, in order to prevent violations of the law by debt collectors, it is necessary to have synchronized regulations from Bank Indonesia and the OJK and involve the Indonesian National Police (Polri) and the Supreme Court of the Republic of Indonesia in completing the preparation of regulations that are synchronized and have norms and objectives that are pre-emptive against law violations by debt. collector as will be described in this paper.